SYNTHESIS AND ANTI-MICROBIAL STUDY OF OXADIAZOLYL INDAZOLES: Life Science-Organic Chemistry - A KUSANUR, RAVIRAJ; MAHESH R (International Journal of Life Science and Pharma Research, 2013)
A rapid and efficient synthesis of substituted N-[(1,3,4-oxadiazol-2-yl)methyl]-4-fluoro-6-phenyl-1Hindazol-3-amines has been reported. The key intermediate is 2-(4-fluoro-6-phenyl-1H-indazol-3-ylamino) acetohydrazide (5), which has been obtained by series of reactions starting from cyclisation of 4-bromo-2, 6- difluoro benzonitrile. All the newly synthesized oxadiazole derivatives were screened for their antimicrobial activity